2003
DOI: 10.1051/forest:2003063
|View full text |Cite
|
Sign up to set email alerts
|

Net effect of competing vegetation on selected environmental conditions and performance of four spruce seedling stock sizes after eight years in Qu�bec (Canada)

Abstract: -A study was established in 1993 to determine the response of four black spruce (Picea mariana) and white spruce (P. glauca) stock sizes on two sites located in Québec (Canada), each representing a different type of competing vegetation. At each site, a split-split-plot design with 15 to 17 replicates was used, in which the presence of competition (weedy and bare plots), seedling initial size, and spruce species were assigned respectively to the whole plot, the subplot, and the sub-subplot. Larger initial seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 34 publications
2
54
1
4
Order By: Relevance
“…Nonetheless, due to serious stem deformations, the prospects of common-sized transplants seem much worse than the prospects of saplings. In this regard we agree with Jobidon (2000) and Jobidon et al (2003) who suggested that early survival of plantation should not be used as a criterion for assessing the severity of weed competition.…”
Section: Discussion Mortality and Mechanical Damagecontrasting
confidence: 36%
See 1 more Smart Citation
“…Nonetheless, due to serious stem deformations, the prospects of common-sized transplants seem much worse than the prospects of saplings. In this regard we agree with Jobidon (2000) and Jobidon et al (2003) who suggested that early survival of plantation should not be used as a criterion for assessing the severity of weed competition.…”
Section: Discussion Mortality and Mechanical Damagecontrasting
confidence: 36%
“…Nonetheless, some implications can be derived from comparison of saplings, semisaplings or large seedlings with common-sized transplants or seedlings, although the studies were conducted mostly on conifers. Schmidt-Vogt and Grüth (1969), Jobidon et al (2003) and Thiffault (2004) reported a greater growth potential and competitive ability of larger planting stock as compared to common stock sizes. According to Van den Driessche (1992), seedlings selected as large in the nursery had significantly greater height than seedlings selected as small throughout the referred period (1984)(1985)(1986)(1987)(1988)(1989)(1990) and absolute size differences increased.…”
Section: Nutrition and Growthmentioning
confidence: 99%
“…However, the relationships between light and growth or morphological parameters are far to be fully understood. Other than to be species-specific, for a certain species these relationships may vary among climatic regions [34] and may be greatly affected by the interaction with other factors 270 G. Grassi, R. Giannini such nutrient availability, sapling size and competition [8,10,16,25,[31][32][33]. This complexity becomes especially relevant in uneven-aged managed forests, where the high structural fragmentation of the canopy and the clustering pattern of natural regeneration [15] lead to a high spatial variability of light in the understory and of competition between saplings.…”
Section: Introductionmentioning
confidence: 99%
“…In a field experiment in subalpine forests of south central British Columbia, Coates [16] found that, throughout the snow free period, soil temperatures at 10 cm depth were about 5 °C higher in soils where competing vegetation was removed than in soils beneath undisturbed vegetation. Smaller, but still notable differences due to vegetation cover were found in an experiment in Quebec [28]. Alexander [1] and Brang [9] both recorded higher soil surface temperatures on soils with a humus layer than on mineral soils.…”
Section: Performance Of Light Treatments and Effects On Soil Temperaturementioning
confidence: 97%
“…Soil temperature within this layer limits root growth [4,16], which starts at a temperature of 8 and 12°C [42] and increases up to about 20 °C [41,42]. Site factors affecting near-surface soil temperatures are air temperature, direct sunlight, vegetation cover [3,16,28], snow cover [3], and soil properties such as water content [38].…”
Section: Introductionmentioning
confidence: 99%